Kinetika Reaksi Sintesis Karboksi Metil Glukomanan - Rahmawati Andayani; Santi Tri Wijayanti; Fadilah fadilah (Equilibrium Journal of Chemical Engineering, 2017)
Cultivation of porang plants now has a promising prospect because it has a higheconomic value. Glucomannan content in porang is quite high (15-64% dry base).Glucomannan, the natural polymers contained in porang corms, can be modified bycarboxymethylation. The synthesis of carboxy methyl glucomannan took place over twosteps, alkalization and carboxymethylation. Alkalization was conduct using NaOH inethanol 70% as the medium. The carboxymethylation steps was conducted by addingsodium chloroacetate as the reagent. The quality of carboxy methyl glucomannan wasdetermined from its Degree of Substitution (DS). The results showed that the highestdegree of substitution was 0.47 with 70% ethanol as medium and at temperature 65oC for 150 minutes reaction time. From the data obtained, it can be seen that the reaction ofglucomannan carboxymethylation proceeded at 1st order reaction, with the collision factorvalue (A) of 491.227 J/mol.K and its activation energy (Ea) of 30,994.59 J/mol.K.